Islam’s Foundational Equality (American Journal of Islam and Society, 2017)
In her Feminist Edges of the Qur’an, Aysha Hidayatullah arguesthat certain Qur’anic verses are incorrigibly male-privilegingand are themselves privileged. Hence, egalitarian readings ofthe Qur’an are unsupported and unsupportable. If, as egalitarianspropose, such verses are unjust, then either the Qur’an isnot God’s word or God is unjust. By contrast (1) I contend thatno evidence suggests any Qur’anic verses are incorrigibly maleprivileging,(2) I provide or indicate egalitarian readings for relevantcontenders, (3) I note that no Qur’anic evidence supportsthe primacy of any such verse. Finally, since controverting egalitarianreadings of such verses are available, the logical formof Hidayatullah’s argument merely shows that if they are readto exhibit injustice, those readings cannot be God’s word. Sincethe Qur’an is God’s word, there is no option but to reread them.